La ausencia de conciliadores en materia penal incide en la eficiencia y eficacia del proceso penal ecuatoriano - Villena Falcones, Héctor Daniel (2017)
This work is based on the absence of a conciliatory conscience at the level of administration of justice; As well as the ignorance and lack of preparation of many of the professionals of the right either of the public sector or of the free exercise of the profession. As a result of which in our country the criminal conduct each day surpasses very considerable figures, we are a society exposed to the appearance and direct affectation of new criminal types or forms of crime without being able to put an end to these typical antijuridic behaviors………